Construction and verification of the autonomous underwater helicopter’s digital twin system for missions simulation - An, Xinyu; Xing, Haisu; Li, Haoda; Shi, Hongbo; Gu, Yang (Ocean engineering, 2025)
•The construction method of a simulation platform for the Autonomous Underwater Helicopter (AUH) based on digital twin technology is introduced, establishing a high-fidelity digital twin model of the AUH along with the corresponding motion controller design.•A spiral dive method for the AUH based on the Line-of-Sight (LOS) guidance law is proposed, and digital twin simulations are conducted with randomly generated ocean current disturbances using a Gaussian-Markov process.•The reliability of the AUH digital twin system is verified through comparisons between digital twin simulations and experimental results from pool path following missions and lake sweeping survey missions. Traditional underwater vehicles face challenges of unsynchronized software and hardware development during their research and application processes. As a novel type of underwater vehicle, the Autonomous Underwater Helicopter (AUH) has an increasing demand for supporting digital twin infrastructure to enhance its performance in underwater operational missions. This study proposes a digital twin framework based on the AUH, which collects key parameters of the physical entity of the AUH, establishes kinematic and dynamic models, designs a motion controller for the AUH, and conducts preliminary digital twin simulations. Then, a complex spiral dive mission is designed, combining the Line-of-Sight (LOS) guidance law with ocean current disturbances generated by a Gaussian-Markov process, to validate the rationality of the AUH digital twin simulation under complex conditions. Finally, the digital twin simulation of path following using an adaptive LOS algorithm maintains an average trajectory error within ±0.5 m compared with pool experiments. The digital twin simulation of the AUH’s sweeping survey maintains an average trajectory error within ±3 m compared with lake experiments. The results demonstrate that the developed AUH digital twin system builds a high-fidelity digital twin prototype and exhibits good reliability and effectiveness in supporting complex underwater operations.